2019 IEEE International Conference on Pervasive Computing and Communications Workshops (PerCom Workshops) 2019
DOI: 10.1109/percomw.2019.8730685
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Security Vulnerabilities in the Belkin WeMo Home Automation Ecosystem

Abstract: The popularity of smart home devices is growing as consumers begin to recognize their potential to improve the quality of domestic life. At the same time, serious vulnerabilities have been revealed over recent years, which threaten user privacy and can cause financial losses. The lack of appropriate security protections in these devices is thus of increasing concern for the Internet of Things (IoT) industry, yet manufacturers' ongoing efforts remain superficial. Hence, users continue to be exposed to serious w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Secure storage could be achieved with the help of a permission oriented operating system running on top of the client application, or with hardware support in the case of embedded devices. For example one could use Zymbit, 11 which provides an encrypted filesystem and key management support, to secure Raspberry Pi (RPi) devices, as those we used in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secure storage could be achieved with the help of a permission oriented operating system running on top of the client application, or with hardware support in the case of embedded devices. For example one could use Zymbit, 11 which provides an encrypted filesystem and key management support, to secure Raspberry Pi (RPi) devices, as those we used in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Security, including authentication, data integrity, and confidentiality, often remain an afterthought. These mixed-up priorities create risks, as IoT devices become susceptible to malware infection [1], services prone to disruption [18], and user data vulnerable to privacy leaks [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Fake command is injected by by an attacker into an IoT device [14]. Say, smart speakers and smart switches may accept fake commands from a local network without authenticating sources [15], [16]. (iv) Command interception.…”
Section: B Attacks On Iot Devicesmentioning
confidence: 99%
“…It is difficult to maintain security at the application layer because of lack of sufficient protocol security services, incorrect configuration, and resource limitations [127]. For example, Liu et al [128] showed that it was possible to emulate a commercial edge device using software and then fooling the associated mobile App to uncover home Wi-Fi passphrases, and to trap the user into disclosing personal information. Similarly, Margulies [129] argued that linking garage door openers to the internet network using mobile Apps might easily pose a security threat.…”
Section: ) Rq4: Smart Home Application Securitymentioning
confidence: 99%